Role of the menstrual cycle on performance and injury risk: A survey of female professional rugby players in the United Kingdom - Hayward, E.; Akam, L.; Hunter, D.; Mastana, S. (International Journal of Environmental Research and Public Health, 2024)
Background: Female athletic performance and injury risk is impacted by variations in the menstrual cycle (MC), but the understanding of the impacts and mechanisms influenced by the menstrual cycle on exercise performance are not fully delineated. Aims and Objectives: Evaluate associations between the menstrual cycle, perceived performance, and injury risk of elite female rugby players using an online survey.